Azithromycin as an add-on treatment for persistent uncontrolled asthma in adults: protocol of a systematic review and meta-analysis. Issue 1 (2nd January 2020) - Liu, Wei; Mu, Wei; Zhang, Huiting; Zhai, Jingbo; Li, Xiaodan; Guan, Peng; Lian, Fu; Feng, Jihong; Yu, Shuangjiang; Wang, Xuepin; Si, Jinhua; Sun, Zengtao; et al.
Abstract : Introduction: Clinical management of asthma remains a public challenge. Despite standard treatment with inhaled corticosteroids (ICS) and long-acting beta-agonists (LABAs), asthma remains uncontrolled in a substantial number of chronic asthma patients who risk reduced lung function and severe exacerbations. Azithromycin could have add-on effects for these patients. This study is proposed to systematically evaluate the efficacy of azithromycin as an add-on treatment for adults with persistent uncontrolled symptomatic asthma. Methods and analysis: Two reviewers will perform a comprehensive search of PubMed, Embase, the Cochrane Central Register of Controlled Trials (CENTRAL) and four Chinese electronic databases including China National Knowledge Infrastructure (CNKI), Chinese Biomedical Literature Database (CBM), WanFang Data and VIP Database from inception to May 2019. Only randomised controlled trials will be included. There is no restriction on language or publication status. Combined oral azithromycin and an ICS or/and a LABA will be compared with standard treatment alone or with a placebo. The primary outcomes are the number or frequency of asthma exacerbations, changes in asthma symptoms and lung function. Secondary outcomes include the number or frequency of inhalations of beta-agonists with or without corticosteroids for rescue use, eosinophil counts in blood or sputum, adverse events and others. A meta-analysis will be attempted to provide an estimate of the pooled treatment effect. Otherwise, qualitative descriptions of individual studies will be given. Ethics and dissemination: Ethical approval is not required because no primary data will be collected. Study findings will be presented at scientific conferences or published in a peer-reviewed journal. PROSPERO registration number: CRD42019117272.